IMPLEMENTASI ENKRIPSI DEKRIPSI PESAN TEKS MENGGUNAKAN MODEL JULIS CAESAR BERBASIS OBJECT ORIENTED PROGRAMME - Reditya Kiko Pandu Pratama; Fitri Latifah (Lembaga Penelitian dan Pengabdian Pada Masyarakat, 2014)
Current data and information become a thing that cannot be separated again. But at a certain moment, we forget the essential aspect, namely the security aspects of such information and data. Therefore we must always be vigilant in terms of data security. Encryption techniques and the description of which writer will apply message text, the security techniques adopted from ancient security techniques, which the writer apply to the programming language. Change from plain text to cipher text is a basic function of encryption techniques and this description. Encryption techniques and my description, using the algorithm of Julius Caesar were able to secure data.